NILAI-NILAI PENDIDIKAN MULTIKULTURAL DALAM FILSAFAT IBN KHALDUN DAN IMPLEMENTASINYA DI SEKOLAH MENENGAH - Mukhtari, Al (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
The thought of Ibn Khaldun, a classical Muslim scholar, contains social values that remain relevant to modern educational challenges, especially within the context of multiculturalism. Amid increasing social tension due to cultural, ethnic, and religious diversity, education is expected to serve as a medium for reconciliation and social integration. This study aims to explore the relevance of Ibn Khaldun's social philosophy to the development of multicultural education in secondary schools in Banda Aceh and to identify concrete implementations of these values in classroom practices. This research employed a descriptive qualitative approach, collecting data through literature review of Ibn Khaldun’s works and in-depth interviews with teachers and students from three schools. Findings indicate that Ibn Khaldun's thought includes values such as tolerance, social justice, and community solidarity, which can be internalized through multicultural learning. Successful implementation models include integrating values into Islamic Religious Education subjects, cross-cultural thematic discussions, and diversity-based social projects. The study concludes that Ibn Khaldun’s philosophy offers an important epistemic foundation for shaping a contextual multicultural education framework in Indonesia. Its implications involve the need for teacher training, strengthening inclusive education policies, and developing a responsive curriculum to address social diversity dynamics.